Answer to Question #10686 in Algebra for nksprasad
factorize a^3+b^3-c^3+3abc
1
2012-06-12T10:44:47-0400
factorize a³+b³-c³+3abc
(a + b + c)(a² + b² + c² + x)
a³ + ab² + ac² + ax
ba² + b³ + c²b + bx
ca² + cb² + c³ + cx
a³, b³, c³ are all valid
ab² + ac² + ba² + c²b + ca² + cb² + ax + bx + cx are not.
They need to cancel out and any variable multiplied on the other side would give you the square of that variable
- ab - bc - ac
This really does check out:
= a^3 + ab² + c²a +a( - ab - bc - ac) +
+ ba² + b³ + bc² + b( - ab - bc - ac) +
+ ca² + cb² + c³ + c(- ab - bc - ac) =
= a³ + b³ + c³ - 3abc
(a + b + c)(a² + b² + c² - ab - bc - ac) =
= a³ + b²a + c²a - a²b - abc - a²c +
+ ba² + b³ + c²b - ab² - b²c - abc +
+ ca² + cb² + c³ - acb -c²b - ac² =
= a³ + b³ + c³ - 3abc.
So,
a³+b³-c³+3abc = (a + b + c)(a² + b² + c² - ab - bc - ac).
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment